Amyloid PET ordering practices in a memory disorders clinic - Katherine W. Turk; Ana Vives‐Rodriguez; Kylie A. Schiloski; Anna Marin; Ryan Wang; Prabhjyot Singh; Gabor P. Hajos; Rachel Powsner; Renée DeCaro; Andrew E. Budson (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction This study assessed the ordering of amyloid positron emission tomography (PET) scans in a Veterans Affairs (VA) memory disorders clinic as part of routine clinical care, with possible implications for the extent to which ordering may occur outside of the VA in the future if covered by insurance. Methods Clinical features predictive of ordering amyloid PET scans were retrospectively assessed; the percentage of patients who met appropriate use criteria were evaluated. Results Among 565 veterans, 34.9% of received an amyloid PET scan and 98.0% of these were consistent with appropriate use criteria. Patients with a PET were younger and more likely to have an initial diagnosis of Alzheimer's disease (AD). Of patients without an amyloid PET scan ordered, 64.4% would have met appropriate use criteria for amyloid PET. Discussion The majority of scans ordered were consistent with appropriate use criteria and more patients were eligible than received a scan. The current study's findings that approximately one‐third of patients in a memory disorders clinic received an amyloid PET scan has implications for memory disorders clinics inside and outside of the US Veterans Health Administration.